Return to sender. - Chakrabarti, Shami (New Statesman, 2009)
The article focuses on the legal status of Gary McKinnon, who is scheduled to be extradited to the U.S. for hacking. The author believes that people should not be extradited to another country without evidence or due consideration given to where they should be tried. Information about the U.S. Extradition Act, which was enacted after September 11, 2001, is provided.